New business ventures and the entrepreneur /Howard H. Stevenson ... [et al.]. - Stevenson, Howard H.New business ventures and the entrepreneur.
Rev. ed. of: New business ventures and the entrepreneur / Howard H. Stevenson. 4th ed. 1994.